NIAT PELANGGAN UNTUK MENGGUNAKAN KEMBALI JASA UMRAH ARWINDA TOUR & TRAVEL - Winda Trisnandawati (Jurnal Bisnis dan Keuangan, 2020)
The porpose of this research is to know how deep customers aim to have Arwinda Tour and Travel as their umrah Travel. This goals of research is to know the quality of Arwinda service around cust’s satisfaction, their trust, and to know how deep they want to use this agent back in their travel. Quantitative is the research metode that author used to know relation between variabels, these are exogenous variabel is quality of service and endogen variabel is satisfaction, trust, and their aim to use this travel agent again. Samples that used was about 150 jamaahs, minimum once a year that have Arwinda Tour and Travel. Analysize technical that author used was Partial Least Square (PLS). The result is it positive influence significally as : Service quality has a positive influence of customers satisfaction, service quality has a positive influence of trust, Cust satisfaction has a influence of a cust’s will to use this travel agent again trust has a positive influence of a cust’s will to use this travel agent again